Impact of Molding Temperature, Fiber Loading and Chemical Modifications on the Physicomechanical, and Microstructural Morphology Properties of Woven Kenaf Fiber/PLA Composites for Non-Structural Applications - Jai Inder Preet Singh; Vikas Sharma; Sehijpal Singh; Vikas Dhawan; Ahmed Belaadi; Rajeev Kumar; Shubham Sharma; Abhinav Kumar; Fuad A. Awwad; M. Ijaz Khan; Emad A. A. Ismail (Journal of Natural Fibers)
These days, green composites are getting a lot of attention for their biodegradability, sustainability, and affordability. This study applies polylactic acid as the matrix and untreated and surface-treated kenaf fibers as reinforcement to fabricate kenaf-reinforced PLA-based composites. Kenaf fibers are exposed to three different chemical treatments (sodium hydroxide, potassium permanganate, and potassium dichromate) and investigate the effect of surface modifications on the mechanical properties of kenaf/PLA composites. The surface modified fibers were characterized by FTIR Spectroscopy. The consequences of processing variables such as fiber volume percent ranging from 25% to 50% and molding temperature range of 160°C to 180°C were also examined on the mechanical characteristics of developed composites and are validated using SEM analysis. Surface modifications result in improved tensile and flexural characteristics of developed treated kenaf/PLA composites. Alkali treated woven kenaf fiber composites with greater matrix adhesion have optimum tensile and flexural strength of 72.81 MPa and 94.45 MPa respectively. The present study revealed that composites (fabricated at 170°C molding temperature) have maximal tensile and flexural strength at 35% fiber volume fraction.